Key factors in the perception of the quality of dental services provided by undergraduate students - Giraldo-Molina, Adriana María; Berbesi-Fernández, Dedsy Yahaira (Revista Facultad de Odontología Universidad de Antioquia, 2017)
Introduction: teaching clinics in health education in Colombia have been extremely important due to the connections between Higher Education Institutions and Health Services Providers, enabling internship services. This study seeks to identify the key factors in the perception of the quality of dental services provided by undergraduate students. Methods: this was a cross-sectional study observing the socio-demographic characteristics of students and patients related to the quality of the health care provided at dental clinics according to factors of students, patients, service assessment, and dental clinics agreements. Results: 70.8% of patients receiving dental services offered through dental clinics perceived the overall quality of the service as excellent; as per distribution by sex, the percentage of women seeking dental services is higher, accounting for 69.3% of the study population. Conclusions: most patients consider that the dental services they receive are excellent, considering both management of their disease and student’s knowledge.